Mitochondria protection with ginkgolide B-loaded polymeric nanocapsules prevents diethylnitrosamine-induced hepatocarcinoma in rats. (March 2014) - Ghosh, Swarupa; Dungdung, Sandhya Rekha; Choudhury, Somsubhra Thakur; Chakraborty, Somsuta; Das, Nirmalendu
Aim: Hepatocellular carcinoma (HCC) has no successful pharmacotherapeutic remedy. The aim of this study was to ascertain whether ginkgolide B (GB)-loaded polymeric nanocapsules can prevent diethylnitrosamine (DEN)-induced HCC in rats.Materials & methods: GB was fabricated in two types of nanocapsules of which one was polyethylene glycol coated (N1GB) and the other was uncoated (N2GB). These nanocapsules were orally gavaged during DEN-induced HCC development in rats.Results: Nanocapsulation of GB enabled aqueous suspension and slow time-dependent release of the compound. Anticarcinogenic potential of N2GB was reflected by its ability in the management of DEN-induced reactive oxygen species generation, mitochondrial dysfunction, p53, NF-κB, inducible nitric oxide synthase, COX-2 and VEGF expressions, and induction of apoptosis in cancer cells in the rat liver.Conclusion: Positive zeta-potential on N2GB surface might have offered higher hepatic accumulation of GB, especially at the electron-dense organelle mitochondria. Mitochondria protection against DEN-induced oxidative damage ensured HCC prevention. Original submitted 27 June 2012; Revised submitted 4 December 2012; Published online 7 June 2013